ANALISA BAHAN BAKAR MINYAK HASIL PIROLISIS SAMPAH PLASTIK JENIS PP DAN PET TERHADAP KINERJA GENERATOR SET PADA PLTSA PLASTIK KAPASITAS 1000 WATT - ., Zurohaina; ,, Tahdid; Zikri, Ahmad; Bow, Yohandri; ,, Zulkarnain; sari, Desi Nurmala; Wulandari, Nila; Putra, M. Rizky Adhitya (Politeknik Negeri Sriwijaya, 2019)
Plastic waste and energy is a big problem nowadays especially for big cities. Along with the growing population every year with a diverse community life activities always generate waste every day and energy consumption is increasing high. The limited of energy dependent on fossil energy forces the search for new alternative energy to replace fossil energy. One of the answers to the limitation of fossil energy is the conversion of plastic waste into liquid fuels by pyrolysis technology using plastic raw materials of Polyethylene Terephthalate (PET) and Polypropylene (PP). Which can be used as fuel in motor fuel or generator set to generate electricity in prototype unit of plastic waste generator by using dry coconut shell as Furnace fuel. The purpose of this research is to test the performance of generator sets using light Oil fuels (FRA) and Heavy Oil Fuel (FRB). Liquid fuels pyrolysis products are used as fuel generators to be converted into electrical energy with loads varying to a maximum load at 1000 watts for 10 hours per day. The results of this research obtained the value at the optimal load of 800 watts of electrical current that occurred at 4.37 amperes with 183 volt voltage, 2650 rpm rotation shaft genset, and fuel consumption / hour at 0.803 L / hour.